HUBUNGAN ANTARA KEGIATAN BERMAIN BENDA ALAM TERHADAP KEMAMPUAN MENGENAL ANGKA ANAK USIA DINI (PENELITIAN DI KELOMPOK B1 RA AL-WAFI PANYILEUKAN KOTA BANDUNG): THE RELATIONSHIP BETWEEN NATURAL MATERIALS PLAY ACTIVITIES AND NUMBER RECOGNITION ABILITY IN EARLY CHILDHOOD (A STUDY IN GROUP B1 RA AL-WAFI PANYILEUKAN, BANDUNG CITY) - Nurfitriyani, Nurfitriyani; Kurnia, Aam; Syamiyah, Syamiyah (Thufuli, 2022)
Research to find out the reality of playing natural objects. Natural objects can be used to recognize numbers. This research was conducted in group B1 RA Al- Wafi Panyileukan Bandung City. The research method is correlational. The research subjects were the children of group B1 RA Al-Wafi Panyileukan Bandung City in the 2018/2019 Academic Year, totaling 18 children. The results of the analysis were 84 from the interval 80 – 100. very good category. The ability to recognize numbers for early childhood can get an average value of 76. This number is in the 70-79 interval with a good category. the correlation coefficient through the Spearman Rank formula (ρ_count) is 0.71. This correlation coefficient is included in the strong category at the interval 0.600-0.799. The results of the significance test obtained t_count = 4.0329 the price of t_table = 2.120. This means that the null hypothesis is rejected and the alternative hypothesis is accepted. Playing natural objects has a significant positive relationship with the ability to recognize numbers in Group B1 RA Al-Wafi Panyileukan Bandung City. The contribution/influence of playing natural objects on the ability to recognize early childhood numbers is 50.41%. there are other factors 49.59% that affect the ability to recognize early childhood numbers.